2019
DOI: 10.20414/jtq.v17i1.944
|View full text |Cite
|
Sign up to set email alerts
|

Pembelajaran Berbasis Digital: Studi Penggunaan Geogebra Berbantuan E-Learning Untuk Meningkatkan Hasil Belajar Matematika

Abstract: Abstrak Penelitian ini menggambarkan pembelajaran berbasis digital, yaitu penggunaan Geogebra berbantuan e-learning, untuk meningkatkan hasil belajar mahasiswa pada konsep bidang dan garis dalam ruang. Penelitian ini adalah pre-experimental dengan jenis one-shot case study dengan partisipan mahasiswa calon dosen matematika pada semester II yang terdiri dari  14 orang laki-laki dan 30 orang perempuan dari salah satu universitas di Indonesia. Hasil penelitian menunjukkan penggunaan Geogebra berbantuan e-learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
0
8
0
2
Order By: Relevance
“…Research on the Rasch model for instrument validation has been carried out by several researchers (Khumaeroh et al, 2017;Maseko, Luneta, & Long, 2019;Nisa et al, 2017;Purnomo, 2016;Susdelina et al, 2018). Meanwhile, several other researchers studied the Rasch model for ability analysis (Folastri, Rangka, & Ifdil, 2017;Sari, Sekarwana, Hinduan, & Sumintono, 2016;Sudihartinih, Purniati, & Rohayati, 2019;Sudihartinih & Wahyudin, 2019a, 2019bWidhiarso & Sumintono, 2016). In this study, instrument validation on plane geometry was not found.…”
Section: Introductionmentioning
confidence: 74%
“…Research on the Rasch model for instrument validation has been carried out by several researchers (Khumaeroh et al, 2017;Maseko, Luneta, & Long, 2019;Nisa et al, 2017;Purnomo, 2016;Susdelina et al, 2018). Meanwhile, several other researchers studied the Rasch model for ability analysis (Folastri, Rangka, & Ifdil, 2017;Sari, Sekarwana, Hinduan, & Sumintono, 2016;Sudihartinih, Purniati, & Rohayati, 2019;Sudihartinih & Wahyudin, 2019a, 2019bWidhiarso & Sumintono, 2016). In this study, instrument validation on plane geometry was not found.…”
Section: Introductionmentioning
confidence: 74%
“…If they do not perform, they put blame on the teachers of not being able to explain a particular concept, whereas those with a high self-efficacy will put more effort into completing any given task [13]. In this case, Sudihartinih and Wahyudin [26] argue that there is a relationship between self-efficacy and the level of geometric thinking, yet it is weak.…”
Section: Student Self-efficacymentioning
confidence: 99%
“…Wherever and whenever both educators and students can communicate and interact virtually. In today's modern era, electronic applications facilitate communication and interaction between educators and students (Sudihartinih & Wahyudin, 2019). In Higher Education, the commonly used learning platforms are the online learning system (SPADA), Zoom Meeting, Google Meet, WhatsApp, Edmodo, Edublogs, Skype, Wikispaces, Schoology, OpenStudy, Quora, Pinterest, and others.…”
Section: Hots-based E-learning In Higher Educationmentioning
confidence: 99%